Influence of oceanic and climate conditions on the early life history of European seabass Dicentrarchus labrax. (July 2021) - Pinto, M.; Monteiro, J.N.; Crespo, D.; Costa, F.; Rosa, J.; Primo, A.L.; Pardal, M.A.; Martinho, F.
Abstract: Understanding how marine fish early-life history is affected in the long-term by environmental and oceanographic factors is fundamental given its importance to population dynamics and connectivity. This work aimed at determining the influence of these processes on the interannual variability in hatch day and early-life growth patterns of European seabass, over a seven-year period (2011–2017) in the Atlantic Iberian coast. To accomplish this, otolith microstructure analysis was used to determine seabass hatch day and to develop early-growth correlations. In most years, hatching occurred from February to April, with two exceptions: in 2012, hatching started in early-January, and in 2016 an exceptionally long hatching period was registered. Using generalized additive models (GAM), we observed that sea surface temperature (SST), the North Atlantic Oscillation index (NAOi) and Chlorophyll-a (Chla) were the main drivers behind the inter-annual variability in seabass hatch day. Analysis of correlations between growth increments allowed assessing important periods of seabass growth and how future growth is affected. Since seawater temperature is among the main drivers for seabass recruitment and growth, its life cycle may be hampered due to ocean warming and an increasingly unstable climate, with consequences for the natural marine stocks and their harvest. Highlights: Impacts on life-cycle will be more hard-felt in more southern European regions. Seabass early life is climate-driven: sea surface temperature is the most influential factor. Timing of hatching has the potential to dictate juvenile connectivity and recruitment. Early growth in the larval period seems to have lasting effects on juvenile seabass.